Will the Transatlantic Trade and Investment Partnership be the engine of free trade? (Economic and Political Thought, 2015)
The Transatlantic Trade and Investment Partnership is an undertakingthat can completely change the contemporary structure of global traderelations. Due to the role and importance of the economic exchange betweenthe parties to the future free trade agreement: the European Union andthe United States, the rules of liberalisation negotiated by them can changethe present, universal order within the WTO system. Having taken intoconsideration the increasing number of agreements that create new freetrade areas, one can say that the thesis that, as a result of that phenomenon,there is an increasing fragmentation of global trade seems to be confirmedin practice. What the benefits are going to be will depend on the balance oftrade changes and development. At the same time, what the costs are going tobe for particular parties to the global economic exchange will mainly dependon their national economies’ ability to meet challenges adequately. It is wellknown that developed countries and their multinational companies cope withsuch conditions best. New rules of global economic exchange are createdand the positive effects of these changes in that exchange concentrate in thisarea. Although there are attempts to make developing countries beneficiariesof the world trade liberalisation, e.g. the Bali Package within the WTO, thepositive effect of these initiatives is more hypothetical than real for them.